Analisis Kesuksesan Website STIKIP PGRI JOMBANG Dengan Menggunakan Model Delone dan Mclean - putra, ekky Anugrah; Sulistiowati, Sulistiowati; Soebijono, Tony (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2019)
STIKIP PGRI Jombang has a website addressing www.stikipjb.ac .id, which is used as an intermediary for information media with students, with the existence of information technology such as websites are expected to provide accurate, complete, relevant information and facilitate communication. The involvement of students in the use of the website, the ease of the website to be used can increase various knowledge of information services to students. To find out the satisfaction, it is used by conducting a success analysis using the Delone and Mclean methods. Data used through questionnaires. and tested the validity of linearity reliability and SEM analysis. System quality variables directly affect user satisfaction with a value of 59.6%, meaning that the quality of the system presented in the website according to respondents' perceptions in this research is good.Â